ANALISIS SELISIH BIAYA PRODUKSI PAKAN TERNAK PADA KUD KARYA BHAKTI NGANCAR - Riyantini Riyantini; Budiono Budiono; Wahyu Suhardono (CAHAYA AKTIVA, 2019)
Analysis of the difference in production costs consists of an analysis of raw material costs, direct labor costs, and factory overhead costs. The results of this difference analysis can be used as a guideline for decision making in corporate management by comparing the results of the analysis of differences in standard production costs with actual production costs.KUD Karya Bhakti Ngancar is a cooperative that has several work units, one of which is the animal feed production unit. The method used by the author is quantitative descriptive which aims to describe the nature of something that has taken place in the event and examine the causes or symptoms that occur in the company.Based on the results of research in 2017 can be seen the following results: Difference in cost of raw materials for pulses and pellets of Rp 62,400  causes of differences in raw material costs is the actual price of raw materials is greater than the price of standard raw materials. The difference in direct labor costs amounting to Rp 1,996,800 causes the difference in direct labor costs because labor rates are actually lower than standard labor rates. Difference in factory overhead costs of Rp 1,332,864, the cause of this difference is the determination of standard prices that are higher than the actual overhead needs. Keyword: Variance Analysis, Cost of Production